2020
DOI: 10.1016/j.rasd.2020.101519
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors that affect university completion for autistic people

Abstract: Background: Autistic individuals may be less likely to complete their university studies, but there is no research to date that examines why this is the case. This study thus examined the factors that may affect university completion for autistic people. Method: Two-hundred and thirty autistic people who had attended university completed an online survey, whereby 151 had graduated on their first attempt, 34 graduated after several attempts, and 45 had not completed. Participants answered questions regarding th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…However, our predictors focused on individual, psychological variables, rather than sociological ones ( Behr et al, 2020 ). We did not measure aspects such as academic skills, transition experiences or fitting in at university, or poor autism acceptance, which past research has indicated may link to dropping out for autistic students ( Cage et al, 2020 ; Cage and Howes, 2020 ). Further theoretical work is needed which considers the role of the wider ecosystem around the student when it comes to dropping out, as has been outlined for autistic students graduating from university ( Vincent and Fabri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our predictors focused on individual, psychological variables, rather than sociological ones ( Behr et al, 2020 ). We did not measure aspects such as academic skills, transition experiences or fitting in at university, or poor autism acceptance, which past research has indicated may link to dropping out for autistic students ( Cage et al, 2020 ; Cage and Howes, 2020 ). Further theoretical work is needed which considers the role of the wider ecosystem around the student when it comes to dropping out, as has been outlined for autistic students graduating from university ( Vincent and Fabri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual number of autistic students at university could be much higher, as many choose not to disclose ( Knott and Taylor, 2014 ) or have experienced barriers to diagnosis ( Huang et al, 2020 ). One additional concern is that many autistic students appear to be more likely to drop out of university than their non-autistic peers ( Newman et al, 2011 ; Cage et al, 2020 ). It is therefore imperative we understand why autistic students might be more likely to drop out, and generally better understand how to improve autistic students’ experiences at university.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-structured interview questions were developed following reviewing of the literature, a quantitative survey ( Cage et al, 2020 ) and one researcher drawing on lived experience as an autistic person who had dropped out of university. Topics included transitioning to university, social experiences, academic experiences and support, and reasons for dropping out.…”
Section: Methodsmentioning
confidence: 99%
“…Little research has looked at non-completion specifically for autistic people, although Gurbuz et al (2019) noted that current autistic students had more thoughts about withdrawing than their non-autistic peers. The current study follows a quantitative survey which examined factors that could contribute to non-completion for autistic people ( Cage et al, 2020 ). The study found difficulties with the transition to university, low social and organisational identification and poorer academic experiences were factors contributing to non-completion.…”
mentioning
confidence: 99%